Temporal lobe proteins implicated in synaptic failure exhibit differential expression and deamidation in vascular dementia - Gallart-Palau, Xavier (2015)
Progressive synaptic failure precedes the loss of neurons and decline in cognitive function in neurodegenerative disorders, but the specific proteins and posttranslational modifications that promote synaptic failure in vascular dementia (VaD) remain largely unknown. We therefore used an isobaric tag for relative and absolute proteomic quantitation (iTRAQ) to profile the synapse-associated proteome of post-mortem human cortex from vascular dementia patients and age-matched controls. Brain tissue from VaD patients exhibited significant down-regulation of critical synaptic proteins including clathrin (0.29 ; p<1.0•10-3) and GDI1 (0.51 ; p=3.0•10-3), whereas SNAP25 (1.6 ; p=5.5•10-3), bassoon (1.4 ; p=1.3•10-3), excitatory aminoacid transporter 2 (2.6 ; p=9.2•10-3) and Ca2+/calmodulin dependent kinase II (1.6 ; p=3.0•10-2) were substantially up-regulated. Our analyses further revealed divergent patterns of protein modification in the dementia patient samples, including a specific deamidation of synapsin1 predicted to compromise protein structure. Our results reveal potential molecular targets for intervention in synaptic failure and prevention of cognitive decline in VaD.